THE RIGHTS OF A PERSON DEPRIVED OF LIBERTY OF MAINTAINING FAMILY TIES IN 5 EUROPEAN COUNTRY - Iulia POPESCU (Challenges of the Knowledge Society)
A prisoner's life can often be a scary way of life for many people, which is why many individuals don’t want to be close to people who have been imprisoned, for obvious reasons. But the reality is that those who execute prison sentences, sooner or later, are liberated from prison and re-enter en society. Resocialization is a hard and difficult process to be fulfilled, but obviously not impossible. In trying to redress the behaviours of those who have chosen the wrong way of life, family involvement is essential, especially in terms of maintaining mental health, and in the hope that at the end of the punishment, at the exit of the penitentiary there will be someone waiting there for them. The present paper aims to analyze the rights of inmates to keep in touch with their families, stipulated in the legislation of 5 European countries, the similarities and possible differences of their approach in the desire to identify the best regulations in this field, with best results in re-socialization. However, it is known that permanent contact with the family increases the confidence in the person self-esteem so that he / she overcomes the bad moments of life, as well as in the case of the prisoners the existence of more rights to maintain contact with the family is a desire